2020
DOI: 10.1111/pedi.13170
|View full text |Cite
|
Sign up to set email alerts
|

Early markers of periodontal disease and altered oral microbiota are associated with glycemic control in children with type 1 diabetes

Abstract: Objectives To determine the relationship between periodontal disease and glycemic control in children with type 1 diabetes and to characterize the diversity and composition of their oral microbiota. Methods Cross‐sectional study including children with type 1 diabetes recruited from clinics at the Women's and Children's Hospital (Australia). Participants had a comprehensive dental assessment, periodontal examination, and buccal and gingival samples collected for 16S rRNA sequencing. Results Seventy‐seven parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 24 publications
0
34
2
Order By: Relevance
“…The higher rates of gingivitis reported in our study could be because of differences in phenotype measurement; Jensen et al, reported on more advanced gingival disease. Previous studies have reported conflicting data regarding the association between glycemic control and oral health, 8,[10][11][12][13][14]25,26,36 possibly due to different inclusion and reporting criteria. In particular, previous studies used different HbA 1c cut-off points to determine glycemic control, different sample sizes (with differing numbers of participants within each group) and different indices to measure caries experience; making it challenging to draw direct comparisons between studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher rates of gingivitis reported in our study could be because of differences in phenotype measurement; Jensen et al, reported on more advanced gingival disease. Previous studies have reported conflicting data regarding the association between glycemic control and oral health, 8,[10][11][12][13][14]25,26,36 possibly due to different inclusion and reporting criteria. In particular, previous studies used different HbA 1c cut-off points to determine glycemic control, different sample sizes (with differing numbers of participants within each group) and different indices to measure caries experience; making it challenging to draw direct comparisons between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Children with T1D may also be at increased risk of dental caries due to changes in dietary practices, oral hygiene habits and altered salivary properties 7,8 . Few studies have investigated the association between glycemic control and oral health in children with T1D, and results to date are inconsistent 5,8–14 …”
Section: Introductionmentioning
confidence: 99%
“…Fusobacterium nucleatum and Campylobacter rectus were more frequently detected, and interleukin (IL)-6 levels were similar between the groups (46). On the other hand, an up-to-date research by Jensen et al (58) demonstrated that worsening glycemic control is associated with increased severity of early markers of periodontal disease in children and adolescents with T1DM. In that study, it was also observed that glycemic control was related to the complexity and richness of the microbiota of the gingival plaque and lower brushing frequency, independent of glycated hemoglobin (HbA1c) (58).…”
Section: Plaque-induced Gingivitis and T1dmmentioning
confidence: 99%
“…On the other hand, an up-to-date research by Jensen et al (58) demonstrated that worsening glycemic control is associated with increased severity of early markers of periodontal disease in children and adolescents with T1DM. In that study, it was also observed that glycemic control was related to the complexity and richness of the microbiota of the gingival plaque and lower brushing frequency, independent of glycated hemoglobin (HbA1c) (58). Thus, well-designed clinical studies are still required to clarify the interplay between diabetes and inflammation of gingival and periodontal tissues.…”
Section: Plaque-induced Gingivitis and T1dmmentioning
confidence: 99%
“…The extent of oral microbial importance to health goes beyond the potential for bacterial pathogenesis infection. Oral health, gum disease, and periodontitis have been found to play a direct role in the development and progression of non-communicable diseases (NCDs), such as obesity ( 35 ), diabetes ( 36 ), and a number of cancers, including colorectal and esophageal cancer ( 37 ). With these insights, attention on the oral microbiome and its corollary relationship to systemic disease has focused on its exciting potential for early diagnostic purposes and intervention of NCDs.…”
Section: Introductionmentioning
confidence: 99%